A comparison of coordination and its variability in lower extremity segments during treadmill and overground running at different speeds - Abbasi, A.; Yazdanbakhsh, F.; Tazji, M. K.; Aghaie Ataabadi, P.; Svoboda, Z.; Nazarpour, K.; Vieira, M. F. (Gait and Posture, 2020)
Background: Recently, the use of treadmills for walking and running has increased due to lifestyle changes. However, biomechanical differences in coordination between running on a treadmill or overground have not been adequately addressed.